ARQUITETURA DE UM SISTEMA DE CONSULTAS E VISUALIZAÇÃO GRÁFICA DA REPRESENTAÇÃO DO CONHECIMENTO CONTIDO NO PUBMED - Machado, Henrique Tamiosso (2009)
In the bioinformatics has a great amount of biological and genetic information that serve of support for research, and each day this amount of information grows more. Diverse research made for many researchers in different areas, as molecular biology, structural biochemist, enzymology, physiology, pathology, among others, comes generating some results and information that must be stored to be used in the diverse forms. But there the problem appears, how to store, to manipulate, to visualize all these information? The bioinformatics uses the computational power to catalogue, to organize, to structuralize and to manipulate these information facilitating the use of these information that are of extreme importance for Biology. The PubMed is a service of the National Library of Medicine of United States that supplies access to more than 18 million citations for periodical scientific articles in the area of health science. In order to consider a new boarding for the search and representation of the knowledge found in the gotten result, this work presents the use of norm ISO 13250 Topic Maps for the creation of semantic nets involving the concepts found in the system of information of the PubMed, the construction of a composed architecture for a data base with deriving information of the PubMed by the National Library of Medicine of the United States (NLM), an interface for different research of the available one for the Entrez system, where it is possible to define priorities for the consultations. Also is possible to make the representation of the knowledge contained in the PubMed through semantic nets and techniques of date mining.